2016
DOI: 10.1155/2016/2585787
|View full text |Cite
|
Sign up to set email alerts
|

An Advanced Orthotopic Ovarian Cancer Model in Mice for Therapeutic Trials

Abstract: A nude mouse received subcutaneous injection of human ovarian cancer cells HO-8910PM to form a tumor, and then the tumor fragment was surgically transplanted to the ovary of a recipient mouse to establish an orthotopic cancer model. Tumors occurred in 100% of animals. A mouse displayed an ovarian mass, ascites, intraperitoneal spread, and lung metastasis at natural death. The mean survival time was 34.1 ± 17.2 days, with median survival time of 28.5 days. The findings indicated that the present mouse model can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…Orthotopic mouse ovarian cancer model was generated in nude mice (female, 6–8 weeks old) as previously described ( 12 ). Briefly, mice were anesthetized with pentobarbital, a 1.5 cm dorsal incision was performed in the kidney region, the left ovarian bursa was exposed and injected with 1×10 6 SKOV3/CDDP or SKOV3/CDDP/miR-199a-3p cells in 50 µl PBS (n=5/group).…”
Section: Methodsmentioning
confidence: 99%
“…Orthotopic mouse ovarian cancer model was generated in nude mice (female, 6–8 weeks old) as previously described ( 12 ). Briefly, mice were anesthetized with pentobarbital, a 1.5 cm dorsal incision was performed in the kidney region, the left ovarian bursa was exposed and injected with 1×10 6 SKOV3/CDDP or SKOV3/CDDP/miR-199a-3p cells in 50 µl PBS (n=5/group).…”
Section: Methodsmentioning
confidence: 99%
“…A higher level of LC3-II in tumor tissues indicated that autophagy was involved in the anticancer effect. Efficacy of this modality should be validated in an orthotopic cancer model, considering limitations of an ectopic model (Zhang et al 2016(Zhang et al , 2017.…”
Section: :1mentioning
confidence: 99%
“…Tumor cells or a solid tumor are applicated intrabursally, i.e., into the bursa ovarica enclosing mouse ovary or directly onto the ovary, thereby reproducing the primary site of tumor growth and disease progression best [ 311 ]. Intrabursal as well as intraperitoneal inoculation allow tumor cells to spread throughout the peritoneal cavity and to attach to serosal surfaces thus representing a well-suited metastatic model [ 312 , 313 ]. It is, however, worth to consider that the bursal enclosure of mouse ovary does not apply to human ovary which restricts accurate imitation of metastasis.…”
Section: Mouse Models In Ovarian Cancer Researchmentioning
confidence: 99%